ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG - Hidayatullah, Afif; Sri Muljaningsih (Journal of Development Economic and Social Studies, 2023)
The increasing population in Indonesia has an impact on the increasing need for jobs. The government has tried to provide jobs in the formal sector, namely in the fields of trade and industry, but this has not been able to solve the problem of the need for increased employment. In the end, workers who became unemployed because they did not get opportunities in employment turned to the informal labor market. One of the most numerous informal sectors in the city of Malang is being a trader in traditional markets. The purpose of this research is to find out and analyze what factors influence the income of traders, namely capital factors, length of business, education level, working time and age. The instrument of this research used a questionnaire. The samples taken were 50 respondents from traders in Blimbing Market, Malang City. Analysis and processing of data using SPSS with the research method of multiple linear regression analysis. The results of this study partially show that the variables of capital and education level have a positive and significant effect on the income of traders. While the length of business, working time, and age have no effect on the income of traders.